Digital Play as Purposeful Productive Literacies in African American Boys. (28th December 2017) - Lewis Ellison, Tisha; Solomon, Marva
Abstract: Digital literacies abound in playing a foundational role in the rhythm and pattern of our lives, yet debates continue about how to harness them to teach and learn literacy. In an effort to humanize digital literacies, this department column offers a vast array of topics, from participatory work that pushes educators and researchers to communicate in local and global spaces to ways of redefining core reading and literacy skills through a screen‐based, multimodal logic. This column also provides a venue for research and practical applications that depict technology use as a part of the fabric of being human. The column helps educators reconceptualize the ways that children learn with technology, media, and new communication systems; honors educator success stories and burning questions and issues; and reimagines literacy futures.